An endangered bird calls less when invasive birds are calling. (27th January 2021) - Hopkins, Jaimie M.; Edwards, Will; Laguna, Juan Mula; Schwarzkopf, Lin
Abstract : Novel noises can affect various animal behaviours, and changes to vocal behaviour are some of the most documented. The calls of invasive species are an important source of novel noise, yet their effects on native species are poorly understood. We examined the effects of invasive bird calls on the vocal activity of an endangered Australian finch to investigate whether: 1) native finch calling behaviour was affected by novel invasive bird calls, and 2) the calls of the finches overlapped in frequency with those of invasive birds. We exposed a wild population of black‐throated finch southern subspecies Poephila cincta cincta to the vocalisations of two invasive birds, nutmeg mannikins Lonchura punctulata and common mynas Acridotheres tristis, a synthetic 'pink' noise, and a silent control. To determine whether the amount of black‐throated finch calling differed in response to treatments, we recorded and quantified black‐throated finch vocalisations, and assessed the amount of calling using a generalised linear mixed model followed by pairwise comparisons. We also measured, for both black‐throated finches and the stimulus noises: dominant, minimum and maximum frequency, and assessed the degree of frequency overlap between black‐throated finch calls and stimulus noises. Compared to silent controls, black‐throated finches called less when exposed to common myna calls and pink noise, but not to nutmeg mannikin calls. We also found that pink noise overlapped most in frequency with black‐throated finch calls. Common myna calls also somewhat overlapped the frequency range of black‐throated finch calls, whereas nutmeg mannikin calls overlapped the least. It is possible that masking interference is the mechanism behind the reduction in calling in response to common myna calls and pink noise, but more work is needed to resolve this. Regardless, these results indicate that the calls of invasive species can affect the behaviour of native species, and future research should aim to understand the scope and severity of this issue.